Effects of intramuscular administration of Platelet-Rich Plasma on denervated muscle after peripheral nerve injury - Soldado, Francisco; López de Jesús, Maider; Beitia, Maider; González-Burguera, Imanol; Ocerin, Garazi; Elejaga-Jimeno, Ainhoa; Saumell-Esnaola, Miquel; Barrondo, Sergio; Oraa, Jaime; Sallés, Joan; Delgado, Diego; García Del Caño, Gontzal; et al. (Connective tissue research, 2025)
After peripheral nerve injury (PNI), prolonged denervation of the target muscle prevents adequate reinnervation even if the nerve is repaired. The aim of this work is to analyze the effect of intramuscular Platelet-Rich Plasma (PRP) in a denervated muscle due to PNI.Materials and. An irreversible PNI was generated in the common peroneal nerve of 80 Wistar rats by nerve resection. Animals were divided into groups: non-treatment (NT), saline (S) and PRP (PRP). 200 uL of saline (S group) and PRP (PRP group) were infiltrated intramuscularly into the tibialis anterior muscle on a weekly basis, from surgery to sacrifice (at 2, 4 and 7 weeks). Muscles were histologically processed for immunofluorescence and Western blotting. Effects on nicotinic acetylcholine receptor (nAChR), satellite cells (SC) and myogenin expression were analyzed. Comparisons were performed by two-way analysis of variance (ANOVA). PRP had a platelet concentration 1.5-fold higher than blood, without erythrocytes and leukocytes. The PRP group had a higher percentage weight than the S and NT groups ( < 0.05). The levels of nAChRα1 and nAChRε subunit were lower in the PRP group relative to the NT and S ( < 0.05), while the nAChRγ subunit showed an increase in the PRP group ( < 0.05). The activation of SCs was higher in the PRP group compared to NT and S groups ( < 0.05). PRP treatment can modulate NMJ configuration as well as key myogenic regulatory factors in denervated muscle, enhancing SC activation while mitigating muscle atrophy.